Low Bordetella pertussis Antibody Seroprevalence Among Mothers and Infants - (:unkn) unknown (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2020)
Objective: The greatest risk of morbidity and mortality from pertussis infection is observed among infants who are 6 months and younger. Therefore protection from pertussis infection is very important during the first 6 months of life. The aim of the study is to assess Bordetella pertussis antibody titers among infants after two doses of pertussis vaccination at 6 months of age. Method: This was a prospective, multicentered cohort study. Paired maternal and infant serum samples were obtained during the first month after delivery and only infant serum samples were again taken at 6 months of age. Serum samples were tested for Bordetella pertussis-IgG by the enzyme-linked immunosorbent assay (ELISA). Results: The study enrolled 209 mother-infant pairs. At one month after delivery 49.7% of mothers and 32.1% of infants had detectable Bordetella pertussis-IgG antibodies. After two doses of DTaP-IPV-Hib vaccine, at 6th months of age, Bordetella pertussis-IgG seroprevalence among infants increased to 43.3%. Conclusion: After 2 doses of DTaP-IPV-Hib, more than half of the infants at 6 months of age had undetectable Bordetella pertussis-IgG and presumed unprotected against pertussis disease. A new strategy of protecting infants from pertussis must be implemented.
Keywords: pertussis; maternal antibody; infant antibody; seroconversion; VACCINE; ENGLAND; SEX